2017
DOI: 10.7150/jca.18197
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Aldolase B Confers a Poor Prognosis for Rectal Cancer Patients Receiving Neoadjuvant Chemoradiotherapy

Abstract: Background: Colorectal cancer is the third most common cancer in both sex worldwide and it is also the fourth most common cause of cancer mortality. For rectal cancer, neoadjuvant concurrent chemoradiotherapy (CCRT) followed by radical proctectomy is gold standard treatment for patients with stage II/III rectal cancer. By data mining a documented database of rectal cancer transcriptome (GSE35452) from Gene Expression Omnibus, National Center of Biotechnology Information, we recognized that ALDOB was the most s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…This again indicates a critical metabolic change, as previously observed in chRCC (27) and in gastric cancer (35). Conversely, an over-expression of gluconeogenic genes and proteins is frequently found in other tumor species, such as the over-expression of ALDOB in ccRCC (36) and colon cancer (37)(38)(39), which was also associated with tumor progression and poor prognosis.…”
Section: Discussionsupporting
confidence: 74%
“…This again indicates a critical metabolic change, as previously observed in chRCC (27) and in gastric cancer (35). Conversely, an over-expression of gluconeogenic genes and proteins is frequently found in other tumor species, such as the over-expression of ALDOB in ccRCC (36) and colon cancer (37)(38)(39), which was also associated with tumor progression and poor prognosis.…”
Section: Discussionsupporting
confidence: 74%
“…Specifically, increased ALDOB expression was found to favor cancer cell proliferation and metastasis in multiple cancers, such as colon cancer (Bu et al, 2018), rectal cancer (Tian et al, 2017), and colorectal adenocarcinoma . This might also be one reason for the low metastatic potential (Volpe et al, 2012) and the high survival rate of chRCC patients (Amin et al, 2002;Przybycin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal changes in ALDOB are associated with a number of diseases, including hereditary fructose intolerance, hepatitis, cirrhosis and cancer ( 64 ). Using data mined from the Gene Expression Omnibus for the colorectal cancer transcriptome (GSE35452) database, Tian et al ( 65 ) reported that ALDOB is associated with glycolysis and is the most significantly increased transcript (GO: 0006096). It may serve a significant role in colorectal cancer progression and the response to neoadjuvant concurrent chemoradiotherapy, and as a novel prognostic biomarker.…”
Section: Discussionmentioning
confidence: 99%